Driving co-engineering in virtual children's museum: using community engagement. - Wang, Zhiwei; Xu, Shuke; Li, Ziqi (Museum Management & Curatorship, 2024)
This study aimed to develop the Sanxingdui Online Children's Museum application jointly. The authors of the study, children aged 12–15, software developers and museum visitors were the co-designers of the application. The collaborative engineering consisted of six consecutive stages of empathizing, defining, ideating, prototyping, testing, and implementing. These stages included a site visit, seminars and consultations, registration, laboratory, and field testing. As expected, the children were more involved in the design process than adults were and reported a high level of acquisition of new knowledge. The stages of empathizing and generating ideas turned out to be especially informative for the children. The field-testing results were satisfactory in terms of usability, functionality, cultural content and gameplay of the application. The paper discusses some collaborative engineering issues at each stage of the study. The work done to create the application has educational value and is important for the preservation of cultural heritage.